2021
DOI: 10.3390/ijms22010406
|View full text |Cite
|
Sign up to set email alerts
|

CK2 Down-Regulation Increases the Expression of Senescence-Associated Secretory Phenotype Factors through NF-κB Activation

Abstract: Senescent cells secrete pro-inflammatory factors, and a hallmark feature of senescence is senescence-associated secretory phenotype (SASP). The aim of this study is to investigate the protein kinase CK2 (CK2) effects on SASP factors expression in cellular senescence and organism aging. Here CK2 down-regulation induced the expression of SASP factors, including interleukin (IL)-1β, IL-6, and matrix metalloproteinase (MMP) 3, through the activation of nuclear factor-κB (NF-κB) signaling in MCF-7 and HCT116 cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…KCNQ1OT1 knockdown increas ROS production, as indicated by the right shift in fluorescence during flow cytome (Figure 2B). It was previously reported that CK2 downregulation induces SASP expr sion [20] and ROS generation [18]. Ectopic expression of CK2α abrogated the induction SASP factor expression and ROS generation, mediated by KCNQ1OT1 downregulat (Figure 2A and B).…”
Section: Kcnq1ot1 Knockdown Induced Sasp Factor Expression and Ros Ge...mentioning
confidence: 53%
See 2 more Smart Citations
“…KCNQ1OT1 knockdown increas ROS production, as indicated by the right shift in fluorescence during flow cytome (Figure 2B). It was previously reported that CK2 downregulation induces SASP expr sion [20] and ROS generation [18]. Ectopic expression of CK2α abrogated the induction SASP factor expression and ROS generation, mediated by KCNQ1OT1 downregulat (Figure 2A and B).…”
Section: Kcnq1ot1 Knockdown Induced Sasp Factor Expression and Ros Ge...mentioning
confidence: 53%
“…Because treatment with LPS causes cellular senescence by downregulating CK2α [20], it was tested whether LPS downregulated KCNQ1OT1 expression. Treatment with LPS (6 µg/µL) reduced the transcript levels of CK2α and KCNQ1OT1 in human cancer cells (Figure 3A).…”
Section: Kcnq1ot1 Was Involved In Lipopolysaccharide (Lps)-mediated S...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, CK2-mediated phosphorylation of SIRT1 at the Ser164 site inhibits its nuclear localization and promotes the progress of non-alcoholic fatty liver (Choi et al, 2017 ), which provides evidence that SIRT1 is involved in the improvement of metabolic diseases. However, A recent study showed that in senescent cells, down-regulation of CK2 can mediate the inactivation of SIRT1, thus activating NF-KB and inducing the expression of senescence-associated secretory phenotype (SASP) factors (Song and Bae, 2021 ). This suggests that SIRT1 accepts negative regulation from CK2, but more evidence is needed to guide us to accurately understand the role of CK2 in different pathological models.…”
Section: The Expression and Activity Of Sirt1 Are Regulated By Many Dimensionsmentioning
confidence: 99%
“…However, senescent cells secrete pro-inflammatory factors through a secretory phenotype associated with senescence that is very particular to this cellular situation. In the paper of Song and Bae [5], the effects of protein kinase CK2 on the expression of some of the factors involved in the senescence-associated secretory phenotype, including interleukin IL-1β, IL-6, and MMP3, were investigated. The data presented here indicate that during the aging process, an enhancement of the senescence-associated secretory phenotype (SASP) occurs through down-regulation of CK2 via dysregulation of NF-κB (IκB) transcription factors and the AKT-IκB kinase axis.…”
mentioning
confidence: 99%